A Pharmacovigilance Study in First Episode of Psychosis: Psychopharmacological Interventions and Safety Profiles in the PEPs Project. (27th October 2015) - Bioque, Miquel; Llerena, Adrián; Cabrera, Bibiana; Mezquida, Gisela; Lobo, Antonio; González-Pinto, Ana; Díaz-Caneja, Covadonga M.; Corripio, Iluminada; Aguilar, Eduardo J.; Bulbena, Antoni; Castro-Fornieles, Josefina; Vieta, Eduard; et al.
Abstract : Background: The characterization of the first episode of psychosis and how it should be treated are principal issues in actual research. Realistic, naturalistic studies are necessary to represent the entire population of first episode of psychosis attended in daily practice. Methods: Sixteen participating centers from the PEPs project recruited 335 first episode of psychosis patients, aged 7 to 35 years. This article describes and discusses the psychopharmacological interventions and safety profiles at baseline and during a 60-day pharmacovigilance period. Results: The majority of first episode of psychosis patients received a second-generation antipsychotic (96.3%), orally (95%), and in adjusted doses according to the product specifications (87.2%). A total of 24% were receiving an antipsychotic polytherapy pattern at baseline, frequently associated with lower or higher doses of antipsychotics than the recommended ones. Eight patients were taking clozapine, all in monotherapy. Males received higher doses of antipsychotic ( P =.043). A total of 5.2% of the patients were being treated with long-acting injectable antipsychotics; 12.2% of the patients received anticholinergic drugs, 12.2% antidepressants, and 13.7% mood stabilizers, while almost 40% received benzodiazepines; and 35.52% reported at least one adverse drug reaction during the pharmacovigilance period, more frequently associated with higher antipsychotic doses and antipsychotic polytherapy (85.2% vs 45.5%, P <.001). Conclusions: These data indicate that the overall pharmacologic prescription for treating a first episode of psychosis in Spain follows the clinical practice guideline recommendations, and, together with security issues, support future research of determinate pharmacological strategies for the treatment of early phases of psychosis, such as the role of clozapine, long-acting injectable antipsychotics, antipsychotic combination, and the use of benzodiazepines.